C-furanosides : synthesis and stereochemistry - Goekjian, Peter; Hauchy, Arnaud; Menhour, Boudjema; Coiffier, Claire (Academic Press, an imprint of Elsevier, 2018)
Carbon analogs of carbohydrates, dubbed C-glycosides, have remained an important and interesting class of mimetics, be it in natural product synthesis, for pharmacological applications, as conformational probes, or for biological studies. C-Furanosides: Synthesis and Stereochemistry provides a much-needed overview of synthetic and stereochemical principles for C-furanosides: analogs of a 5-membered ring carbohydrate glycoside (furanoside), in which the anomeric oxygen has been replaced with a carbon. While our understanding of conformational behavior and of stereoselective synthesis in 6-membered ring compounds is quite good, our ability to predict the conformation of 5-membered ring compounds, or to predict the stereochemical outcome of a given reaction, remains anecdotal. Through a comprehensive review of literature approaches to the different C-furanoside stereoisomers, as well as an interpretation of the outcome in terms of a reasonable number of stereochemical models, C-Furanosides: Synthesis and Stereochemistry enables the reader to determine the best approach to a particular C-glycoside compound, and also hopes to provide a certain level of rationalization and predictability for the synthesis of new systems.